Heredity - Paterson, David William Horn (The University of Edinburgh, 1901)
The recognition of the Principle of Heredity extends back to the early Greeks and Romans. Plato and Lucretius both compare the succession of lives to-the racers with torches in the games of the Athen- ian festival to Vulcan: thus Plato, "Handing on life to one another as a lamp (Or torch) ", and Lucretius, "And in a short space the generation of living beings are changed and like runners hand on the torch of life." Osborn in his book "From the Greeks to Darwin ", MacMillan & Co., 1894, p.27, says "The not- ion of hereditary transmission of characters was extremely ancient, and was naturally founded upon the early observed likeness of offspring to parents. Aristotle also commented upon the principles of the prepotency of the characteristics of one parent over the other, as well as of Atavism." He says:- i.e. Aristotle "Children resemble their parents not only in congenital characters, but in these acquired later in life. For cases are known where parents have been marked by scars, and children have shewn traces of these scars at the same pàints; a case is also reported from Chalcedon in which a father had been branded with a letter, and the same letter some- what blurred and not sharply defined appeared upon the arm of his child."

It is of great interest to note that the system of Lycùrgus established by him nearly 800 years E.C. did not omit regulations regarding marriage and children, "whose welfare was even before their birth a concern to the republic ", Gillies History of An- cient Greece, Vol.I, p.141. Lycurgus argued that the physical qualities of children depend largely on the constitution of their parents, while likewise the "generous and brave produce the brave and good.." The Spartan women were not degraded, as in some other countries of Greece to drudgery, as Lycurgus believed that women so degraded were incapable of bearing good sons to the state, but were.expected to take as their chief employment the performance of offices of domestic economy and to prepare food and clothes for themselves and families. Marriage although regarded as a duty could only be contracted in the full vigour of age, and it is stated that those regulations produced a beneficial effect in the physical condition of the Spartans. Lycurgus lived. in. the infancy of society, regarding which state Gillies says "men are occupied with the business of the present hour, forgetful of the past, and careless of the future." The system instituted by this famous legislater of Sparta was, however, superior in many respects to some customs with which we are not unfamiliar to -day. In this connection the words of Darwin may well be quoted "Man scans with scrupulous care the characters and pedigree of his horses, cattle and dogs, before he mates them. But when he comes to his own marriage, he rarely or never takes any such care. He is impelled by nearly the same mot- ives as the lower animals when they are left to their own free choice, though he is so far superior to them that he highly values mental charms and virtues. On the other hand, he is stronly attracted by mere wealth or rank. Yet he might by selection do some- thing not only for the bodily constitution and frame of his offspring but for their intellectual and moral qualities. Both sexes ought to refrain from marriage if they are in any marked degree in- ferior in body or mind, p.617 Descent of Man.

Haeckel, in his "Evolution of Man ", p.I03, referring to the same subject, at a later period than Darwin, says "In this respect many of the higher animals exercise a better taste and a more impartial judg- ment than does man. But even among men, sexual selection has given rise to a noble form of family life which is the chief foundation in which civil- isation and social states have been built. The human race certainly, owes its origin in great measure to the perfected sexual selection which our ancestors exercised in the choice of wives."